Preparation method and stripping method of large-size strippable hexagonal boron nitride
By using chemical vapor deposition method and pulse growth mode to grow hexagonal boron nitride on sapphire substrates, the problem of difficulty in achieving large-size multi-layer hexagonal boron nitride growth in traditional methods is solved, and the preparation of large-size peelable hexagonal boron nitride and the combination of industrial substrates is achieved, with efficient and controllable growth characteristics.
Patent Information
- Application Number
- CN202311344621.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-17
- Publication Date
- 2025-04-18
AI Technical Summary
It is difficult for the prior art to grow large-sized multi-layer hexagonal boron nitride on sapphire substrates, and it is difficult for traditional methods to achieve rapid growth of hexagonal boron nitride and the combination of industrialized substrates.
Hexagonal boron nitride was grown on the sapphire substrate by chemical vapor deposition. The AlON layer was formed by nitriding the c-side sapphire substrate, and the boron and ammonia were alternately passed through the pulse growth mode to regulate the growth time to obtain large-size peelable hexagonal boron nitride of different thicknesses.
It realizes the growth of large-sized peelable hexagonal boron nitride on a sapphire substrate, which has high material quality, high growth rate and controllable growth thickness, which can be effectively peeled and transferred to the surface of other materials to protect or improve the thermal conductivity of the material.
Smart Images

Figure CN119852163A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of semiconductor preparation, and in particular to a preparation method of large-size peelable hexagonal boron nitride and a peeling method thereof. Background Art
[0002] The structure of hexagonal boron nitride (h-BN) is similar to that of graphene, and the lattice constant By sp 2 It is composed of hybrid, strong covalent and highly polarized BN bonds along the plane. The layers are connected by van der Waals weak interaction forces. Each layer of h-BN is composed of B and N atoms, arranged in a honeycomb structure, and is often called "white graphene". Van der Waals force is a weak interatomic force, which is two to three orders of magnitude weaker than the ionic bonds and covalent bonds in three-dimensional materials. With the help of this weak interlayer van der Waals force, h-BN can be easily peeled off from the substrate material and then used to design and manufacture flexible devices. h-BN also has physical properties such as high mechanical strength, high thermal conductivity, and high oxidation resistance. The peeled-off film can also be used to protect other materials or enhance the heat dissipation capacity of other materials.
[0003] At present, h-BN is usually grown on copper foil by chemical vapor deposition, using the catalytic effect of copper metal to promote the nucleation and growth of h-BN. However, after h-BN covers the metal substrate, the metal substrate loses its chemical catalytic activity, making it difficult to achieve the rapid growth of large-scale multilayer h-BN. In addition, copper foil is not a common substrate for chip design. h-BN needs to be transferred to silicon substrates or sapphire substrates commonly used in industrialization before it can continue to grow and design flexible devices. Therefore, it is urgent to combine the growth of h-BN with industrial substrates, grow large-scale peelable hexagonal boron nitride on sapphire substrates, and peel large-scale hexagonal boron nitride. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] In response to the above problems, the present disclosure provides a preparation method of large-sized peelable hexagonal boron nitride and a peeling method thereof, which are used to at least partially solve the technical problems that traditional methods are difficult to achieve the growth of large-sized multilayer hexagonal boron nitride.
[0006] (II) Technical solution
[0007] On the one hand, the present disclosure provides a method for preparing large-sized peelable hexagonal boron nitride, comprising: S1, nitriding the surface of a c-plane sapphire substrate to form an AlON layer; S2, using chemical vapor deposition, utilizing a pulsed growth mode, introducing boride and ammonia to react on the surface of the AlON layer, and obtaining large-sized peelable hexagonal boron nitride of different thicknesses by regulating the growth time.
[0008] According to an embodiment of the present disclosure, the reaction gas for nitridation treatment in S1 is ammonia, the carrier gas is hydrogen, the temperature is 1000-1300° C., the pressure is 10-100 Torr, and the reaction time is 1-5 min.
[0009] According to an embodiment of the present disclosure, the AlON layer in S1 is an alloy layer generated by the reaction of ammonia gas and a sapphire substrate.
[0010] According to an embodiment of the present disclosure, the chemical vapor deposition method in S2 is metal organic chemical vapor deposition; the pulse growth mode includes alternately introducing boride and ammonia into the reaction chamber in the form of pulses; wherein, the boride is introduced each time for 1 to 4 seconds, and the ammonia is introduced each time for 2 to 8 seconds.
[0011] According to an embodiment of the present disclosure, the boride is one of triethylboron or boron trichloride, and the heating temperature of the boride is 18-24°C; the carrier gas is hydrogen, and the flow rate of hydrogen is 10-60 sccm; the flow rate of ammonia is 100-4800 sccm.
[0012] According to an embodiment of the present disclosure, the growth temperature of the reaction in S2 is 1000-1600° C., the pressure is 10-100 Torr, and the carrier gas is hydrogen.
[0013] According to the embodiments of the present disclosure, the growth time in S2 is 2 to 100 minutes, and the thickness of the obtained large-sized peelable hexagonal boron nitride is 0.5 to 200 nm, and the size includes two inches.
[0014] On the other hand, the present disclosure provides a method for stripping large-sized peelable hexagonal boron nitride, comprising: mechanically stripping the hexagonal boron nitride; wherein the hexagonal boron nitride is prepared according to the above-mentioned method for preparing large-sized peelable hexagonal boron nitride.
[0015] According to an embodiment of the present disclosure, mechanical peeling includes peeling the hexagonal boron nitride from the sapphire substrate using an adhesive tape, and the adhesive tape is a thermal release tape.
[0016] According to an embodiment of the present disclosure, mechanical peeling includes: sticking a thermal release tape on the surface of hexagonal boron nitride; pressing a weight of 1 to 10 kg on the thermal release tape, leaving it to stand for 0.1 to 12 hours, tearing off the thermal release tape and completely peeling off the large-sized hexagonal boron nitride from the surface of the sapphire substrate.
[0017] (III) Beneficial effects
[0018] The preparation method and stripping method of large-sized peelable hexagonal boron nitride provided by the present disclosure, hexagonal boron nitride is grown on a sapphire substrate by chemical vapor deposition, and the hexagonal boron nitride is evenly spread on the surface of the sapphire substrate to obtain large-sized hexagonal boron nitride; by regulating the growth time, hexagonal boron nitride of different thicknesses is obtained, and the stripping characteristics of hexagonal boron nitride are studied, and the large-sized hexagonal boron nitride is stripped off and can be transferred to the surface of other materials to protect it or improve the thermal conductivity of the material, and AlGaN-based devices can be directly grown on the hexagonal boron nitride to design a peelable flexible device, thereby realizing industrialized integrated growth. Among them, the present disclosure also adopts a pulse growth mode, and the boride and ammonia are alternately introduced into the reaction chamber in the form of pulses, and the boride and ammonia will not be introduced into the reaction chamber at the same time. This growth mode can weaken the parasitic reaction between the boride and ammonia, and can ensure the high material quality, high growth rate and controllable growth thickness of the hexagonal boron nitride. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The schematic diagram of the process of preparing large-sized peelable hexagonal boron nitride according to the embodiment of the present disclosure is shown;
[0020] Figure 2 The schematic diagram of the structure of large-sized peelable hexagonal boron nitride prepared according to the embodiment of the present disclosure is shown;
[0021] Figure 3 A schematic diagram of a pulse growth mode according to an embodiment of the present disclosure is schematically shown;
[0022] Figure 4 The schematic diagram of the process of hexagonal boron nitride stripping according to the embodiment of the present disclosure is schematically shown;
[0023] Figure 5 Schematically showing a photograph of 0.5-10 nm hexagonal boron nitride according to an embodiment of the present disclosure;
[0024] Figure 6 Schematically shows the Raman spectrum of 0.5-10 nm hexagonal boron nitride according to the embodiment of the present disclosure;
[0025] Figure 7A transmission electron microscope morphology image of 0.5-10 nm hexagonal boron nitride according to an embodiment of the present disclosure is schematically shown;
[0026] Figure 8 Schematically showing a photo of a partial area after 10-40 nm hexagonal boron nitride is peeled off according to an embodiment of the present disclosure;
[0027] Fig. 9 A schematic diagram shows a partial self-stripping photograph of 40-60 nm hexagonal boron nitride according to an embodiment of the present disclosure;
[0028] Fig.10 Schematically shows a self-stripping photograph of 60-200 nm hexagonal boron nitride according to an embodiment of the present disclosure;
[0029] Description of reference numerals:
[0030] 1, hexagonal boron nitride; 2, AlON layer; 3, sapphire substrate; 4, pulse mode of triethylboron; 5, pulse mode of ammonia; 6, thermal release tape; 7, heavy object; 8, platinum metal electrode. DETAILED DESCRIPTION
[0031] In order to make the objectives, technical solutions and advantages of the present disclosure more clearly understood, the present disclosure is further described in detail below in combination with specific embodiments and with reference to the accompanying drawings.
[0032] The terms used herein are only for describing specific embodiments and are not intended to limit the present disclosure. The terms "comprise", "include", etc. used herein indicate the existence of the features, steps, operations and / or components, but do not exclude the existence or addition of one or more other features, steps, operations or components.
[0033] Various directional words in the present disclosure, such as "front", "back", "left", "right", "up", "down", etc., are only for the convenience of description and are used to describe the relative position relationship between the various components, rather than to limit the present disclosure. Different product placement methods of the present disclosure may result in changes in the various directional descriptions.
[0034] All terms (including technical and scientific terms) used herein have the meanings commonly understood by those skilled in the art, unless otherwise defined. It should be noted that the terms used herein should be interpreted as having a meaning consistent with the context of this specification, and should not be interpreted in an idealized or overly rigid manner.
[0035] The present disclosure provides a method for preparing large-sized peelable hexagonal boron nitride, see Figure 1-2, including: S1, nitriding the surface of the c-plane sapphire substrate 3 to form an AlON layer 2; S2, using chemical vapor deposition, using a pulse growth mode, introducing boride and ammonia to react on the surface of the AlON layer, and by adjusting the growth time, obtaining large-sized peelable hexagonal boron nitride 1 with different thicknesses.
[0036] The method disclosed in the present invention adopts chemical vapor deposition to grow hexagonal boron nitride 1 on a sapphire substrate 3. The hexagonal boron nitride 1 is evenly spread over the surface of the sapphire substrate 3, and a large-sized hexagonal boron nitride 1 can be obtained. By adjusting the growth time, hexagonal boron nitrides of different thicknesses are obtained, and the peeling characteristics of the hexagonal boron nitride are studied. The large-sized hexagonal boron nitride can be peeled off and transferred to the surface of other materials to protect them or improve the thermal conductivity of the materials. AlGaN-based devices can also be directly grown on the hexagonal boron nitride, and peelable flexible devices can be designed to achieve industrial integrated growth.
[0037] On the basis of the above embodiment, the reaction gas for nitridation treatment in S1 is ammonia, the carrier gas is hydrogen, the temperature is 1000-1300° C., the pressure is 10-100 Torr, and the reaction time is 1-5 min.
[0038] The purpose of the nitridation treatment is to infiltrate nitrogen atoms into the surface of the sapphire substrate to form Al-N bonds for the subsequent growth of hexagonal boron nitride. The reaction temperature of the nitridation treatment within the above range is conducive to accelerating the nitridation reaction process. Preferably, the temperature of the nitridation treatment is 1300°C, the pressure is 50 Torr, and the reaction time is 5 minutes.
[0039] On the basis of the above-mentioned embodiment, the AlON layer 2 in S1 is an alloy layer produced by the reaction of ammonia gas and the sapphire substrate 3 .
[0040] Ammonia gas reacts with the sapphire substrate to replace oxygen atoms with nitrogen atoms, 2 O 3 Some of the oxygen atoms in the AlON are replaced by nitrogen atoms to form an AlON alloy layer. The outermost layer of the alloy layer is nitrogen atoms with dangling bonds, which is conducive to the subsequent adsorption and reaction of boron atoms to form BN.
[0041] On the basis of the above-mentioned embodiment, the chemical vapor deposition method in S2 is metal-organic chemical vapor deposition (MOCVD); the pulse growth mode includes alternately introducing boride and ammonia into the reaction chamber in the form of pulses; wherein, the boride is introduced for 1 to 4 seconds each time, and the ammonia is introduced for 2 to 8 seconds each time.
[0042] MOCVD is an epitaxial growth technology commonly used in industry for mass growth of III-nitride materials such as AlN, GaN, and AlGaN. It is also suitable for growing hexagonal boron nitride. The pulse growth mode refers to the process of alternately introducing boride and ammonia into the reaction chamber in the form of pulses. The boride and ammonia will not be introduced into the reaction chamber at the same time. Figure 3 As shown, 4 represents the pulse mode of triethylboron, and 5 represents the pulse mode of ammonia. This pulse growth mode can weaken the parasitic reaction between the boride and ammonia, and can ensure the high material quality, high growth rate and controllable growth thickness of hexagonal boron nitride. Preferably, the boride is introduced for 1 second each time, and the ammonia is introduced for 2 seconds each time.
[0043] Based on the above embodiments, the boride is one of triethylboron or boron trichloride, the heating temperature of the boride is 18-24°C; the carrier gas is hydrogen, the flow rate of hydrogen is 10-60 sccm; the flow rate of ammonia is 100-4800 sccm.
[0044] The boride is triethylboron or boron trichloride, which has the advantages of easy decomposition of B atoms and easy desorption of the remaining reaction products from the substrate. The heating temperature of the boride is within the above range, which is conducive to the carrier gas carrying the boride. Preferably, the boride is triethylboron, the heating temperature of the boride is 18°C, the flow rate of hydrogen is 10sccm or 20sccm, and the introduction time of hydrogen is 36min; the flow rate of ammonia is 2000sccm.
[0045] On the basis of the above-mentioned embodiment, the growth temperature of the reaction in S2 is 1000-1600° C., the pressure is 10-100 Torr, and the carrier gas is hydrogen.
[0046] The growth temperature of the reaction in S2 is in the above range, which is conducive to the growth of hexagonal boron nitride. Preferably, the growth temperature is 1460° C. and the pressure is 50 Torr.
[0047] On the basis of the above-mentioned embodiment, the growth time in S2 is 2 to 100 minutes, and the thickness of the obtained large-sized peelable hexagonal boron nitride is 0.5 to 200 nm, and the size includes two inches.
[0048] The growth time in S2 within the above range is conducive to obtaining hexagonal boron nitride of target thickness. This method can grow hexagonal boron nitride on a two-inch sapphire substrate to obtain large-sized peelable hexagonal boron nitride. Preferably, the growth time is 2-5 min, 5-20 min, 20-30 min, 30-100 min, and the corresponding hexagonal boron nitride thickness is 0.5-10 nm, 10-40 nm, 40-60 nm, 60-200 nm, respectively. The longer the growth time, the thicker the hexagonal boron nitride obtained.
[0049] The present disclosure also provides a method for stripping large-sized strippable hexagonal boron nitride, comprising: mechanically stripping hexagonal boron nitride 1; wherein the hexagonal boron nitride 1 is prepared according to the above-mentioned method for preparing large-sized strippable hexagonal boron nitride.
[0050] Hexagonal boron nitride of different thicknesses exhibits different peeling characteristics, from thin to thick, they are non-peelable, large-sized hexagonal boron nitride can be peeled off using tape, and large-sized hexagonal boron nitride can be self-peeled off.
[0051] Specifically, when the thickness of hexagonal boron nitride is 0.5 to 10 nm, the surface of hexagonal boron nitride is transparent and continuous, and the hexagonal boron nitride cannot be mechanically peeled off from the substrate using tape. When the thickness of hexagonal boron nitride is 10 to 40 nm, the surface of hexagonal boron nitride is transparent and continuous, and the hexagonal boron nitride can be completely mechanically peeled off from the substrate using tape. When the thickness of hexagonal boron nitride is 40 to 60 nm, a small part of the surface of the hexagonal boron nitride has a wrinkle morphology visible to the naked eye, indicating that the hexagonal boron nitride has undergone a certain degree of self-peeling, and the hexagonal boron nitride can be mechanically peeled off from the substrate using tape. When the thickness of hexagonal boron nitride is 60 to 200 nm, the surface of the hexagonal boron nitride is covered with wrinkles visible to the naked eye, indicating that the hexagonal boron nitride has undergone complete self-peeling, and the hexagonal boron nitride can be mechanically peeled off from the substrate using tape.
[0052] On the basis of the above embodiment, the mechanical peeling includes peeling the hexagonal boron nitride 1 off the sapphire substrate 3 using an adhesive tape, and the adhesive tape is a thermal release tape 6 .
[0053] The thermal release tape is helpful for peeling the hexagonal boron nitride off the substrate, and is also helpful for subsequently releasing the hexagonal boron nitride from the tape at a certain heating temperature.
[0054] Based on the above embodiment, mechanical peeling includes: sticking a thermal release tape 6 on the surface of the hexagonal boron nitride 1; pressing a weight 7 of 1 to 10 kg on the thermal release tape 6, leaving it alone for 0.1 to 12 hours, tearing off the thermal release tape 6 and completely peeling off the large-sized hexagonal boron nitride 1 from the surface of the sapphire substrate 3.
[0055] Press a heavy object on the surface of the thermal release tape and let it stand for a while to make the thermal release tape and the hexagonal boron nitride evenly contact, which is conducive to completely peeling off the hexagonal boron nitride.
[0056] The method disclosed in the present invention combines the growth of hexagonal boron nitride with an industrialized substrate, and grows large-sized peelable hexagonal boron nitride on a sapphire substrate, and the large-sized hexagonal boron nitride can be peeled off by using an adhesive tape.
[0057] The present disclosure is further described below through specific implementation methods. The preparation method of the above-mentioned large-size peelable hexagonal boron nitride and its peeling method are specifically described in the following examples. However, the following examples are only used to illustrate the present disclosure, and the scope of the present disclosure is not limited thereto.
[0058] Example 1
[0059] A large-sized exfoliable hexagonal boron nitride is prepared by the following method:
[0060] Figure 1 The schematic diagram of the structure according to the implementation of the present disclosure is shown schematically, which includes a sapphire substrate 3, an AlON layer 2 and a hexagonal boron nitride 1 from bottom to top.
[0061] According to the structural diagram, the preparation of large-sized peelable hexagonal boron nitride specifically includes the following steps:
[0062] (1) A two-inch c-plane sapphire substrate 3 is placed on a graphite tray in an MOCVD growth chamber, and ammonia and hydrogen are introduced into the growth chamber. Ammonia is the reaction gas in the nitridation process, and hydrogen is the carrier gas. The pressure in the growth chamber is reduced to 50 Torr, and the temperature in the growth chamber is raised to 1300°C. The nitridation treatment time is 5 min.
[0063] (2) After the nitridation treatment, the growth chamber pressure is maintained at 50 Torr and the growth chamber temperature is increased to 1460° C. to prepare for the growth of hexagonal boron nitride.
[0064] (3) The pulse growth mode is used to grow hexagonal boron nitride. The group III source is triethyl boron and the group V source is ammonia. First, the pneumatic valve controlling the ammonia is opened and ammonia is introduced for 2 seconds, while the pneumatic valve controlling the triethyl boron is in the closed state. Then, the pneumatic valve controlling the ammonia is closed and the pneumatic valve controlling the triethyl boron is opened and triethyl boron is introduced for 1 second. This is a cycle in which triethyl boron and ammonia are alternately introduced into the growth chamber. The specific pulse mode information is as follows: Figure 3 As shown, they are pulse mode 4 of triethylboron and pulse mode 5 of ammonia. The flow rate of triethylboron is 20 sccm, and the flow rate of ammonia is 2000 sccm. The pressure of the growth chamber is maintained at 50 Torr, the growth temperature is maintained at 1460°C, and the carrier gas is maintained at hydrogen.
[0065] (4) By adjusting the growth time, the thickness of hexagonal boron nitride can be changed. When the growth time is 2-5 min, 5-20 min, 20-30 min, and 30-100 min, the corresponding h-BN thickness is 0.5-10 nm, 10-40 nm, 40-60 nm, and 60-200 nm, respectively. The thickness of h-BN is measured using an ellipsometer.
[0066] Example 2
[0067] A large-size hexagonal boron nitride is peeled off by the following method:
[0068] Due to the weak van der Waals force between hexagonal boron nitride and the substrate, hexagonal boron nitride can be peeled off from the sapphire substrate and easily transferred to the surface of other materials. Due to the lattice mismatch and thermal mismatch between hexagonal boron nitride and the sapphire substrate, hexagonal boron nitride will be affected by the sapphire lattice during its growth, and will also be affected by the different thermal expansion coefficients between different materials during the cooling process, causing a certain amount of stress in the overall layer of hexagonal boron nitride. As the thickness increases, the above stress will continue to accumulate and continuously offset the van der Waals force between the hexagonal boron nitride and the substrate, weakening the adhesion ability of the hexagonal boron nitride on the substrate.
[0069] The present invention discloses mechanical exfoliation to exfoliate hexagonal boron nitride and explores the effect of the thickness of hexagonal boron nitride on exfoliation.
[0070] The mechanical stripping method adopted in the present disclosure is to use a thermal release tape to strip the grown hexagonal boron nitride. The schematic diagram of the stripping process is as follows: Figure 4 First, the thermal release tape 6 is attached to the surface of the hexagonal boron nitride 1, as shown. Figure 4 As shown in (a); then a weight 7 of 1 to 10 kg is pressed on the thermal release tape 6 for a static value of 0.1 to 12 hours. The sum of the adhesive force between the hexagonal boron nitride 1 and the thermal release tape 4 and the stress existing in the entire hexagonal boron nitride layer will be greater than the van der Waals force between the hexagonal boron nitride 1 and the sapphire substrate 3, as shown in FIG. Figure 4 Then, the edge of the thermal release tape 6 is clamped with tweezers, and the thermal release tape 6 is slowly torn off from the surface of the wafer. The hexagonal boron nitride 1 will be adhered to the thermal release tape 6 and peeled off from the sapphire substrate 3 together with the thermal release tape 6, as shown in FIG. Figure 4 As shown in (c); Finally, a large-sized hexagonal boron nitride was obtained after complete peeling. Figure 4 As shown in (d).
[0071] Comparative Example 1
[0072] A large-sized hexagonal boron nitride is peeled off. The peeling conditions are as follows:
[0073] When the growth time of hexagonal boron nitride is 2 to 5 minutes, the thickness of hexagonal boron nitride is 0.5 to 10 nm. Figure 5 As shown, the surface of the hexagonal boron nitride is uniform, transparent and continuous, covering the entire two-inch sapphire substrate surface, which indicates that the growth of large-size hexagonal boron nitride has been achieved.
[0074] Figure 6The Raman spectrum of hexagonal boron nitride is shown in Figure 1. The Raman peak is at 1367.7 cm -1 , which is a typical Raman peak of hexagonal boron nitride.
[0075] Figure 7 This is the TEM, i.e. transmission electron microscope, morphology image of the hexagonal boron nitride. From bottom to top, they are sapphire substrate 3, AlON layer 2, hexagonal boron nitride layer 1, and platinum metal electrode 8 added during testing. There are clear interfaces between the layers, which is consistent with the above-mentioned growth steps of hexagonal boron nitride.
[0076] Since the thickness of hexagonal boron nitride is relatively thin, the stress in the entire hexagonal boron nitride layer due to lattice mismatch and thermal mismatch is relatively small, and the sum of this stress and the adhesive force between the hexagonal boron nitride and the thermal release tape is much smaller than the van der Waals force between the hexagonal boron nitride and the substrate. Therefore, when the thermal release tape is used for mechanical peeling of hexagonal boron nitride in this thickness range, the hexagonal boron nitride cannot be mechanically peeled off from the substrate.
[0077] Comparative Example 2
[0078] A large-sized hexagonal boron nitride is peeled off. The peeling conditions are as follows:
[0079] When the growth time of hexagonal boron nitride is 5 to 20 minutes, the thickness of the hexagonal boron nitride is 10 to 40 nm, and the surface of the hexagonal boron nitride is uniform, transparent and continuous.
[0080] At this thickness, the stress in the hexagonal boron nitride layer due to lattice mismatch and thermal mismatch is relatively large. The sum of this stress and the adhesive force between the hexagonal boron nitride and the thermal release tape can offset most of the van der Waals force between the hexagonal boron nitride and the substrate. Applying a partial tearing force to the thermal release tape can peel the hexagonal boron nitride under the thermal release tape from the substrate. The specific peeling situation is as follows Figure 8 As shown, the light transparent area in the figure is the exposed substrate after the hexagonal boron nitride is peeled off, while the darker area is the hexagonal boron nitride that is not peeled off using the thermal release tape.
[0081] Comparative Example 3
[0082] A large-sized hexagonal boron nitride is peeled off. The peeling conditions are as follows:
[0083] When the growth time of hexagonal boron nitride is 20 to 30 minutes, the thickness of hexagonal boron nitride is 40 to 60 nm. Most of the surface of hexagonal boron nitride is uniform, transparent and continuous, but some areas have wrinkles visible to the naked eye, such as Fig. 9 Shown in black circle.
[0084] At this thickness, the stress in the hexagonal boron nitride layer due to lattice mismatch is very large. The stress in some areas of the hexagonal nitride layer can even directly offset the van der Waals force between the hexagonal boron nitride and the substrate. As a result, self-peeling occurs in some areas. The hexagonal boron nitride can be easily peeled off using thermal release tape.
[0085] As the thickness of hexagonal boron nitride increases, the self-peeling area will gradually increase and slowly cover the entire sheet.
[0086] The sum of the adhesive force between the hexagonal boron nitride and the thermal release tape and the stress existing in the entire hexagonal boron nitride layer is greater than the van der Waals force between the hexagonal boron nitride and the substrate.
[0087] Comparative Example 4
[0088] A large-sized hexagonal boron nitride is peeled off. The peeling conditions are as follows:
[0089] When the growth time of hexagonal boron nitride is 30 to 100 minutes, the thickness of hexagonal boron nitride is 60 to 200 nm. The surface of hexagonal boron nitride is covered with wrinkles visible to the naked eye, such as Fig.10 shown.
[0090] At this thickness, the stress in the hexagonal boron nitride layer due to lattice mismatch is very large. The stress in all areas of the hexagonal boron nitride layer can directly offset the van der Waals force between the hexagonal boron nitride and the substrate. Therefore, the entire hexagonal boron nitride undergoes complete self-stripping, and the hexagonal boron nitride can be easily peeled off using thermal release tape.
[0091] In summary, large-sized, peelable hexagonal boron nitride was successfully grown on a two-inch sapphire substrate using the metal organic chemical vapor deposition method and the pulsed growth mode. The hexagonal boron nitride prepared by this preparation method not only has an area of two inches, but also has the advantages of fast growth rate, controllable growth thickness, peelability, and compatibility with commonly used equipment and substrates in the industry. Due to the lattice mismatch and thermal mismatch between hexagonal boron nitride and the sapphire substrate, different stresses exist in hexagonal boron nitride layers of different thicknesses, reflecting different types of peeling characteristics. The surface of hexagonal boron nitride of 0.5 to 10 nm is transparent and continuous, and the hexagonal boron nitride cannot be mechanically peeled off from the substrate using tape. The surface of hexagonal boron nitride of 10 to 40 nm is transparent and continuous, and the hexagonal boron nitride can be completely mechanically peeled off from the substrate using tape. A small amount of wrinkles visible to the naked eye appear on the surface of 40-60nm hexagonal boron nitride, indicating that the hexagonal boron nitride has undergone a certain degree of self-stripping, and the hexagonal boron nitride can be mechanically peeled off from the substrate using tape. The surface of 60-200nm hexagonal boron nitride is covered with wrinkles visible to the naked eye, indicating that the hexagonal boron nitride has undergone complete self-stripping, and the hexagonal boron nitride can be mechanically peeled off from the substrate using tape. After the large-sized hexagonal boron nitride is peeled off, it can be transferred to the surface of other materials to protect it or improve the thermal conductivity of the material, or AlGaN-based devices can continue to be directly grown on the hexagonal boron nitride, and strippable flexible devices can be designed to achieve industrial integrated growth.
[0092] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0093] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present disclosure. It should be understood that the above description is only a specific embodiment of the present disclosure and is not intended to limit the present disclosure. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present disclosure should be included in the protection scope of the present disclosure.
Claims
1. A method for preparing large-sized peelable hexagonal boron nitride, characterized in that: include: S1, performing nitridation treatment on the surface of a c-plane sapphire substrate (3) to form an AlON layer (2); S2, using chemical vapor deposition method and pulse growth mode, introducing boride and ammonia to react on the surface of the AlON layer, and obtaining large-sized peelable hexagonal boron nitride (1) of different thicknesses by adjusting the growth time.
2. The method for preparing large-size peelable hexagonal boron nitride according to claim 1, characterized in that: In the nitridation treatment in S1, the reaction gas is ammonia, the carrier gas is hydrogen, the temperature is 1000-1300° C., the pressure is 10-100 Torr, and the reaction time is 1-5 min.
3. The method for preparing large-sized peelable hexagonal boron nitride according to claim 2, characterized in that: The AlON layer (2) in the S1 is an alloy layer produced by the reaction of the ammonia gas and the sapphire substrate (3).
4. The method for preparing large-size peelable hexagonal boron nitride according to claim 1, characterized in that: The chemical vapor deposition method in S2 is metal organic chemical vapor deposition; The pulse growth mode includes alternately introducing boride and ammonia into the reaction chamber in the form of pulses; wherein the boride is introduced for 1 to 4 seconds each time, and the ammonia is introduced for 2 to 8 seconds each time.
5. The method for preparing large-sized peelable hexagonal boron nitride according to claim 4, characterized in that: The boride is one of triethylboron or boron trichloride, and the heating temperature of the boride is 18-24° C.; the carrier gas is hydrogen, and the flow rate of the hydrogen is 10-60 sccm; The flow rate of the ammonia gas is 100-4800 sccm.
6. The method for preparing large-sized peelable hexagonal boron nitride according to claim 1, characterized in that: The growth temperature of the reaction in S2 is 1000-1600° C., the pressure is 10-100 Torr, and the carrier gas is hydrogen.
7. The method for preparing large-size peelable hexagonal boron nitride according to claim 1, characterized in that: The growth time in S2 is 2 to 100 minutes, and the thickness of the obtained large-sized peelable hexagonal boron nitride is 0.5 to 200 nm, and the size includes two inches.
8. A method for stripping large-size strippable hexagonal boron nitride, characterized in that: include: Mechanically exfoliate the hexagonal boron nitride (1); wherein the hexagonal boron nitride (1) is prepared according to the method for preparing large-size exfoliable hexagonal boron nitride according to any one of claims 1 to 7.
9. The method for stripping large-size strippable hexagonal boron nitride according to claim 8, characterized in that: The mechanical peeling comprises peeling the hexagonal boron nitride (1) off the sapphire substrate (3) using an adhesive tape, wherein the adhesive tape is a thermal release adhesive tape (6).
10. The method for stripping large-size strippable hexagonal boron nitride according to claim 9, characterized in that: The mechanical stripping comprises: Attaching the thermal release tape (6) to the surface of the hexagonal boron nitride (1); A weight (7) of 1 to 10 kg is pressed on the thermal release tape (6), and the tape is left to stand for 0.1 to 12 hours. The thermal release tape (6) is then torn off and the large-sized hexagonal boron nitride (1) is completely peeled off from the surface of the sapphire substrate (3).